Sanktionierung und Rückfälligkeit von Heranwachsenden - Palmowski, Nina (Universitätsverlag Göttingen, 2019)
Two different sanctioning systems are applicable to young adult offenders in Germany: juvenile criminal law and adult criminal law. The present study provides an overview of the various sanctions applied to these adolescents aged between 18 and 20 and of their reconvictions during an observation period. Based on data from the German Federal Central Criminal Register (Bundeszentral- und Erziehungsregister), the study covers all convictions and juvenile diversional measures in a specific reference year. This data set allows a detailed examination of the applied sanctions and measures, the proportion of juvenile and adult criminal law, and the reconviction rate differentiated by gender, age, offence and other variables. The empirical analysis also addresses regional differences in sanctioning and examines, if juvenile criminal law is "milder" and/or more effective than adult criminal law - questions that play an essential role in the debate on suitable sanctions for young adults.